Material system analysis: A novel multilayer system approach to correlate EU flows and stocks of Li‐ion batteries and their raw materials. (17th March 2022) - Matos, Cristina T.; Mathieux, Fabrice; Ciacci, Luca; Lundhaug, Maren Cathrine; León, María Fernanda Godoy; Müller, Daniel Beat; Dewulf, Jo; Georgitzikis, Konstantinos; Huisman, Jaco
Abstract: Lithium‐ion batteries (LIBs) will play a crucial role in achieving decarbonization and reducing greenhouse gases. If the EU wants to be competitive in the global market of LIBs, it has to ensure a sustainable and secure supply of the raw materials needed for the manufacturing of these batteries. Limited understanding of how the battery material cycles are linked with raw materials supply chains may hinder policy measures targeting the set‐up of a domestic supply chain in the EU since no precise information on where to intervene will be available. The novelty of this work lies in a multilayer system approach developed to reveal interlinkages between the flows of five raw materials contained in LIBs (cobalt, lithium, manganese, natural graphite, and nickel) in the EU. This was achieved by aligning material system analysis datasets of raw materials contained in LIBs with datasets on stocks and flows of this type of batteries in the EU. The results demonstrate the EU's strong import dependency on LIBs and battery raw materials. The EU recycling of lithium and natural graphite is low/nonexistent hindering the sustainable supply of these materials. The results also show that the majority of battery materials are increasingly accumulated in use or hoarding stocks. The proposed approach is designed to help identify bottlenecks and possible solutions to increase the efficiency of the EU LIB system, which could go unnoticed if each material supply chain were examined individually. This study also highlights how the lessons learned can support EU resource‐management policies.